The Crosstalk between Myeloid Derived Suppressor Cells and Immune Cells: To Establish Immune Tolerance in Transplantation - Chao Zhang; Shuo Wang; Cheng Yang; Ruiming Rong (Journal of Immunology Research)
Myeloid derived suppressor cells (MDSCs) are a heterogeneous population of myeloid precursor and progenitor cells and endowed with a robust immunosuppressive activity in multiple pathophysiological conditions. Recent studies have uncovered the crosstalk between MDSCs and immune cells (i.e., natural killer cells, dendritic cells, macrophages, natural killer T cells, and regulatory T cells) and its role in the establishment and maintenance of immune tolerant microenvironment in transplantation. Considering their strong immunosuppressive capability, MDSCs could become a prospective clinical regimen during transplantation tolerance induction, resulting in long-term graft survival with decreased or without immunosuppressive drugs. The review summarized recent research advances in this field and looked ahead at the research directions in the future.